The Role of Knowledge Management Dimension to Improve the Performance of MSMEs in the Digital Era - Anugrah, Fadli; Efrianto, Efrianto; Hamdani, Deky; Sari, Ayu Esteka (Forum Kerjasama Pendidikan Tinggi, 2025)
This study aims to measure the impact of knowledge management dimensions—knowledge generation, knowledge sharing, and knowledge utilization—on the performance of Micro, Small, and Medium Enterprises (MSMEs) in the digital era. Knowledge management is increasingly recognized as a critical factor in enhancing business performance, particularly for MSMEs that face challenges in adapting to technological advancements. The research was conducted in Kerinci Regency, with a sample of 100 MSME entrepreneurs selected using a purposive sampling technique. The study employs the Structural Equation Model (SEM) with AMOS to analyze the relationships among variables and test the proposed hypotheses. The findings indicate that the dimensions of knowledge management, including knowledge generation, knowledge sharing, and knowledge utilization, have a significant and positive impact on MSME performance. Specifically, knowledge management contributes significantly to digital transformation, with an effect size of 70.7%, suggesting that MSMEs that effectively manage knowledge are more likely to adopt and integrate digital technologies into their operations. Furthermore, the combined influence of knowledge management and digital transformation on MSME performance is both substantial and statistically significant, with an effect magnitude of 56.6%. These results highlight the essential role of knowledge management in driving digital transformation and improving business outcomes for MSMEs.This study provides valuable insights for policymakers, business practitioners, and researchers by emphasizing the importance of developing knowledge management strategies tailored to MSMEs. Future research should explore other moderating variables, such as organizational culture and technological readiness, to further understand the dynamics of knowledge management in the digital transformation of MSMEs.